Circulating levels of microRNA 423‐5p are associated with 90 day mortality in cardiogenic shock. (24th November 2018) - Jäntti, Toni; Segersvärd, Heli; Tolppanen, Heli; Tarvasmäki, Tuukka; Lassus, Johan; Devaux, Yvan; Vausort, Mélanie; Pulkki, Kari; Sionis, Alessandro; Bayes‐Genis, Antoni; Tikkanen, Ilkka; Lakkisto, Päivi; et al.
Abstract: Aims: The role of microRNAs has not been studied in cardiogenic shock. We examined the potential role of miR‐423‐5p level to predict mortality and associations of miR‐423‐5p with prognostic markers in cardiogenic shock. Methods and results: We conducted a prospective multinational observational study enrolling consecutive cardiogenic shock patients. Blood samples were available for 179 patients at baseline to determine levels of miR‐423‐5p and other biomarkers. Patients were treated according to local practice. Main outcome was 90 day all‐cause mortality. Median miR‐423‐5p level was significantly higher in 90 day non‐survivors [median 0.008 arbitrary units (AU) (interquartile range 0.003–0.017) vs. 0.004 AU (0.002–0.009), P = 0.003]. miR‐423‐5p level above median was associated with higher lactate (median 3.7 vs. 2.4 mmol/L, P = 0.001) and alanine aminotransferase levels (median 68 vs. 35 IU/L, P < 0.001) as well as lower cardiac index (1.8 vs. 2.4, P = 0.04) and estimated glomerular filtration rate (56 vs. 70 mL/min/1.73 m 2, P = 0.002). In Cox regression analysis, miR‐423‐5p level above median was associated with 90 day all‐cause mortality independently of established risk factors of cardiogenic shock [adjusted hazard ratio 1.9 (95% confidence interval 1.2–3.2), P = 0.01]. Conclusions: In cardiogenic shock patients, above median level of miR‐423‐5p at baseline is associated with markers of hypoperfusion and seems to independently predict 90 day all‐cause mortality.